Popular Preparatory Course for the High School National Exam: a way of Social Inclusion in Itabira (Research, Society and Development, 2020)
This work is a case-study that analyzes the popular preparatory course for the High School National Exam - ENEM, offered by the Universidade Federal de Itajubá (Unifei) – Campus Avançado de Itabira since 2011 as an extension activity.  The group Conexão de Saberes em Física em Popularização da Ciência, part of the Tutorial Education Program/PET collaborates and administrates the course. Free face-to-face classes and learning aids are provided to prepare High School students and alumni from the public educational system. The work is aimed at reporting the number of participants that applied and were admitted to one of the nine Engineering programs at Unifei/Itabira between 2014 and 2018 after participating in the preparatory course. A quantitative case-study methodology was adopted, and the results demonstrated admission rates varying from 25 to 40%. The course was shown to facilitate the access of the local community to the public university and helps Unifei students develop extensionist and pedagogic skills. It also contributes to a positive exposition of the university to the society. Therefore, the project is of great importance to the community as a social inclusion tool.